Gender differences in educational aspirations and attitudes - Rampino, Tina; Taylor, Mark P. (Colchester, 2013)
"We use data from the youth component of the British Household Panel Survey to examine gender differences in educational attitudes and aspirations among 11-15 year olds. While girls have more positive aspirations and attitudes than boys, the impacts of gender on children’s attitudes and aspirations vary significantly with parental education level, parental attitudes to education, child’s age and the indirect cost of education. Boys are more responsive than girls to positive parental characteristics, while educational attitudes and aspirations of boys deteriorate at a younger age than those of girls. These findings have implications for policies designed to reduce educational attainment differences between boys and girls as they identify factors which exacerbate the educational disadvantage of boys relative to girls."